Unilateral Sanctions in International Law and the Enforcement of Human Rights The Impact of the Principle of Common Concern of Humankind - Bogdanova, Iryna (World Trade Institute Advanced Studies, 2022)
Are unilateral economic sanctions legal under public international law? How do they relate to the existing international legal principles and norms? Can unilateral economic sanctions imposed to redress grave human rights violations be subjected to the same legal contestations as other unilateral sanctions? What potential contribution can the recently formulated doctrine of Common Concern of Humankind make by introducing substantive and procedural prerequisites to legitimise unilateral human rights sanctions? Unilateral Sanctions in International Law and the Enforcement of Human Rights by Iryna Bogdanova addresses these complex questions while taking account of the burgeoning state practice of employing unilateral economic sanctions.